How do you solve x^2 +6x +8 =0 using the quadratic formula?

2 Answers
May 8, 2018

The answers are x=-2 and x=-4.

Explanation:

To start, the quadratic formula is x=(-bpmsqrt(b^2-4ac))/(2a)

In this problem, a = 1 (as the x^2 term has no coefficient), b=6, and c=8.

Plug those values into the quadratic equation to get:

x=(-6pmsqrt(6^2-4(1)(8)))/(2(1))

Multiply 2*1 on the bottom of the fraction:

x=(-6pmsqrt(6^2-4(1)(8)))/(2)

Square 6 and multiply 4*1*8 within the square root:

x=(-6pmsqrt(36-32))/(2)

Subtract 36-32 inside the root:

x=(-6pmsqrt(4))/(2)

Solve for sqrt(4)

x=(-6pm2)/(2)

If the pm is positive, you get

x=(-6+2)/(2), which simplifies to x=(-4)/(2), or color(red)(-2)

If the pm is negative, you get

x=(-6-2)/(2), which simplifies to x=(-8)/(2), or color(red)(-4)

May 8, 2018

x = -2 or x = -4

Explanation:

The quadratic formula looks like
x = (-b +- sqrt(b^2 - 4ac))/(2a)

You have...
ax^2 + bx + c = 0
and your equation...
x^2 + 6x +8 = 0

With that you can do...
x^2 +6x + 8 = 0
a = 1
b = 6
c = 8

Then you substitute what you have into the quadratic formula
When you do that you get...
x = (-(6) +- sqrt((6)^2 - 4(1)(8)))/(2(a))

The '+-' means that your going to have 2 answers like x = this or that so, you can just solve the whole equation using '+' first then use '-' next.

when you do that you'll get an answer of x = -2 or -4